The Improving of Synonyms in The Speech of Primary School Students (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article explores the concept of synonymy and its content, the development of skills in the appropriate use of synonyms in speech situations that elementary students may encounter, and its development. Methods of step-by-step teaching of synonyms to young students in the process of primary education, the use of textbooks in the activation of synonyms in students’ speech, as well as increasing the level of mastery of the phenomenon of synonymy in the native language. referred to.